The development of student assessment marks application / Aishah Haris - Haris, Aishah (2006)
A web application is an application delivered to users from a web server over a network such as the World Wide Web or an intranet. The activities involved are data input, processing of data to information, storage of data and information, and the production of outputs. The Student Assessment Marks Application is developed for the Faculty of Information Technology and Quantitative Sciences, and to be implemented online in order to make ease of the lecturers in managing and producing their students' carry marks and for providing better options for the students in viewing their assessment marks. The purpose of this project is to identify the current practice of evaluating the carry marks and what are the criteria or elements involve in calculating them. The research is carried out by conducting a survey, making interviews, and by doing a literature search. Based on the analysis of data obtained, most of the lecturers are using Microsoft Excel in calculating the students' assessment marks, while the students are able to view their marks in front of the lecturer's office. Besides, it is identified that the lecturers are evaluating the students based on the elements such as quizzes, tests, projects and assignments. The Student Assessment Marks Application is developed and successfully tested to few users in order to identify its strength and weaknesses. Findings show that this application has met its aims as proposed. This application is easy to use and also provides easy information retrieval. It is found out that assurance is the most significant for the users followed by reliability when using the application online. After a few modifications, the application is implemented and will be monitored continuously to ensure enough support and is well maintained.